People's Republic of China : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1997)
This Selected Issues paper analyzes state-owned enterprise (SOE) development and reform in China. The paper discusses the role of state ownership in the Chinese economy, providing a 'snapshot' of key features of the state sector, and a review of the growth, efficiency, and profitability of SOEs. The paper argues that economic performance in SOEs has declined in the last few years as evidenced by falling profitability, increasing losses, growing industrial inventories, and low rates of capacity utilization in some sectors. The paper also examines banking sector development and policy issues in China.